(untitled) (Annals of Medical Research, 2021)
Aim: Aortic knob width (AKW) and calcification (AKC) were shown to be associated with atherosclerosis. We aimed to evaluate the relationship between AKW, AKC, and the extensivity of lower extremity arterial disease (LEAD).Material and Methods: AKW and AKC were assessed in patients with LEAD who underwent conventional or CT angiography. Characteristics of patients were retrospectively reviewed.Results: AKC was observed in 79 (42.2%) of 187 patients. Patients with AKC were older compared to those without (63.7±9.4 vs 60.2±8.9; p:0.009). Smoking was more frequent in patients with AKC whereas the frequency of coronary artery disease, hypertension (HT), dyslipidemia (DL), diabetes mellitus (DM) were similar. AKW was greater in patients with AKC (37.6±2.7 mm vs 36.7±2.4 mm; p: 0.013). Patients with AKC had higher TASC II class (2.8 ±0.9 vs 2.4±0.9; p:0.001). Patients were divided into low (A,B)(n:81) and high (C,D)(n:106) TASC II groups. Male patients were more common in both groups albeit statistical difference (%93.8 vs %82.1; p:0.017). DM, HT, and AKC were more common in high TASC II group. AKW was greater in high TASC II group (38.0±2.5 vs 35.8±1.9, p:0.001). HT [OR: 5,956 (2.800-12.671); p:0.001], AKW [OR: 1,583 (1.302-1.926); p:0.001] and AKC [OR: 2,540 (1.185-5.441); p: 0.017] were predictors for high TASC II class in multivariate logistic regression. In ROC analysis, AKW greater than 36.5 mm had 72.6% sensitivity and 69.1% specificity [AUC: 0.766, p:0.01, 95% CI (0.698–0.834)] to predict high TASC II class.Conclusion: AKW and AKC, easily assessed with plain chest radiograph, are related to extensivity of LEAD.Keywords: Atherosclerosis; aortic knob; lower extremity arterial disease; peripheral arterial disease; vascular calcification.